Real-time fault diagnosis method for low-voltage power line carrier communication network based on network topology. Issue 3 (31st August 2021) - Wang, Hao; Huang, Hai; Chen, Anxin; Li, Xiaoqing; Li, Fangui
In order to overcome the problems of long diagnosis time, high cost and low accuracy in traditional communication network fault diagnosis methods, a real-time fault diagnosis method based on network topology for low-voltage power line carrier communication network is proposed. Detect the fault features around the communication network, get the original fault feature set, input the support vector machine, get the optimal feature subset of the low-voltage power line carrier communication network, use the optimal feature subset to construct the network topology structure, collect different fault information on the protection line, form the fault matrix and calculate, so as to get the optimal feature of the low-voltage power line carrier communication network. It can realise the accurate diagnosis of faults. The experimental results show that the fault diagnosis time of this method is less than 10 s, the accuracy of fault diagnosis is up to 95%, and the cost is low.